2016
DOI: 10.5812/jjnpp.33561
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, Anti-Proliferative and Apoptotic Effects of Tribulus terrestris L. Fruit Extract on Human Prostate Cancer Lncap and Colon Cancer HT-29 Cell Lines

Abstract: Background: The medicinal herb Tribulus terrestris L. (Zygophyllaceae) has been used for a long time to treat various kinds of diseases including hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In this regard, 250 and 500 mg/kg of TT extract by improving antioxidant and anti-apoptotic pathways led to an improvement in the cardiac function of rats with cardiac ischemia, although in some markers, a higher dose had more favorable effects (11). The researchers found that 85 and 50 mg/kg of hydroalcoholic extract of TT significantly improved lipid profile in rats with coronary heart disease induced by injecting isoproterenol (13). Moreover, 0.3, 7.1, and 8.7 µg/mL of TT significantly reduced TNFL and FasL levels in the cell and induced apoptosis in cancer cells (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, 250 and 500 mg/kg of TT extract by improving antioxidant and anti-apoptotic pathways led to an improvement in the cardiac function of rats with cardiac ischemia, although in some markers, a higher dose had more favorable effects (11). The researchers found that 85 and 50 mg/kg of hydroalcoholic extract of TT significantly improved lipid profile in rats with coronary heart disease induced by injecting isoproterenol (13). Moreover, 0.3, 7.1, and 8.7 µg/mL of TT significantly reduced TNFL and FasL levels in the cell and induced apoptosis in cancer cells (12).…”
mentioning
confidence: 99%
“…TT with its antioxidant and anti-inflammatory effects improves fat metabolism and appears to inhibit inflammatory and apoptotic activities of tumor necrosis factor-alpha ligand (TNFL) and FasL as well as cell death (13). In this regard, 250 and 500 mg/kg of TT extract by improving antioxidant and anti-apoptotic pathways led to an improvement in the cardiac function of rats with cardiac ischemia, although in some markers, a higher dose had more favorable effects (11).…”
mentioning
confidence: 99%
“…A previous report on T. terrestris extract showed cytotoxic effects on fibroblast cell lines [75]. Moreover, Pourali M, et al, found higher cytotoxicity in colon and prostate cancer cell line assays than in normal fibroblast cell lines [74].…”
Section: Discussionmentioning
confidence: 84%
“…The IC 50 values of 179.62 and 189.70 µg/mL were obtained with methanol and aqueous extract, respectively. Similarly, studies also reported the cytotoxicity activity of alcoholic, hydroalcoholic, and aqueous extracts of T. terrestris [72][73][74]. It was observed that T. terrestris extract does not have much cytotoxic effect on normal cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…While colon cancer cell viability was 10 % at 0.5 ppm, no cytotoxicity was observed on prostate cancer. At 12 ppm, the viability of prostate and cancer cells was reported as 10 % and 30 %, respectively [25]. In addition, the aqueous extracts of this plant obtained by ultrasonic wave assisted extraction and these extract's cytotoxicity was investigated on Hepa 1c1c7 and Ovcar 3 cells.…”
Section: Mtt Assaymentioning
confidence: 99%